Distributed energy storage systems for power networks - Wang, Junbo. (2011)
With the rapid development of the economy and society, the consumption of energy shows continuous increase. However, earth fossil fuel resources are finite and therefore with the depletion of the fuel resources, so we need a new and sustainable resource to substitute the fossil fuels. Due to their clean, renewable and environmental-friendly characteristics, renewable energy sources can be actively considered.